1986
DOI: 10.1111/j.1476-5381.1986.tb09472.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and antiarrhythmic activity of ajmaline in rats subjected to coronary artery occlusion

Abstract: 1 The pharmacokinetics and the antiarrhythmic action of intravenous ajmaline were investigated in anaesthetized rats subjected to coronary artery occlusion. 2 Ajmaline (0.125-2mg kg', i.v. given just after occlusion) suppressed arrhythmias in a dosedependent manner, judged by the reduction of premature ventricular complexes. The incidence of malignant arrhythmias (ventricular tachycardia and fibrillation) was preferentially suppressed at the higher doses of ajmaline (I and 2 mg kg-'). 3 Coronary occlusion indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Hence the AV conduction system might also be a possible site of drug action in rats subjected to coronary artery occlusion; and drugs which slow AV conduction might exert an antiarrhythmic effect. In this respect we have already shown that ajmaline slows AV conduction and that left coronary artery occlusion does not affect the negative dromotropic activity of ajmaline (Hashimoto et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hence the AV conduction system might also be a possible site of drug action in rats subjected to coronary artery occlusion; and drugs which slow AV conduction might exert an antiarrhythmic effect. In this respect we have already shown that ajmaline slows AV conduction and that left coronary artery occlusion does not affect the negative dromotropic activity of ajmaline (Hashimoto et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…It is known that in anaesthetized rats, ischaemic arrhythmias start 5 min after coronary artery occlusion and last for about 10min (Hashimoto et al, 1986). On the other hand, the incidence of reperfusion-induced arrhythmias is dependent on the duration of the preceding occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the negative dromotropic action of ajmaline for the AV conduction system can be quantitatively assessed by measuring the PQ interval in rats (Hashimoto et al, 1986) and dogs (Yasuhara et al, 1987). On the other hand, changes in the extent of the plasma protein binding have been shown to affect the responses of some antiarrhythmic drugs, including lignocaine (Rick et al, 1987) and disopyramide (Huang & 0ie, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…As a model drug, we selected a Class I antiarrhythmic drug ajmaline, the dromotropic action of which on atrioventricular conduction can be assessed by measuring PQ intervals on the electrocardiogram in rats (Hashimoto et al, 1986). Because the pharmacological effects of ajmaline have been shown to be affected by plasma protein binding (Yasuhara et al, 1987), the dromotropic activity in hyperthyroid rats was determined from the plasma unbound concentration.…”
Section: Introductionmentioning
confidence: 99%